Designing Development Policies for the Social Security Retirement System with a Future Study Approach - Shamiri, Mohammad; Amirnejad, Ghanbar; Jaber Ansari, MohammadReza; Derakhshan, Rostam (International Journal of Innovation Management and Organizational Behavior (IJIMOB), 2023)
Objective: This study aims to explore and design development policies for the social security retirement system using a futures research approach, identifying potential future scenarios and formulating strategic responses. Methods: Utilizing a meta-synthesis of existing literature, expert surveys, and scenario analysis, the study systematically identifies key components, challenges, and opportunities within the retirement system, integrating futures research methodologies to project possible future states and policy implications. Findings: The study reveals a comprehensive set of governance, social, cultural, economic, and technological factors that are pivotal in shaping the future of the social security retirement system. It also outlines several potential future scenarios, ranging from optimistic to pessimistic, with corresponding strategic actions and policies designed to address the identified challenges and leverage opportunities. Conclusion: The research concludes that a holistic and adaptive approach to policy design, incorporating futures research, is essential for the sustainable development of the social security retirement system. It emphasizes the need for continuous reform, innovation, and stakeholder engagement to navigate the complexities of future societal and economic landscapes.